Rheological Basics of the Adjusted Theory on the Plant Stems Sliding Cutting - Altunyan, A. V.; Tarverdyan, A. P. (ՀԱԱՀ հիմնադրամ)
The second article of the series considers the method of theoretical solution to the problem of plants stems sliding cutting with the account for the rheological properties of the material. In the result of solving the differential equation for the behavior of rheological model selected for the stem, the normal and tangential stresses at the contact zone of blade and stem interaction have been determined. The basic stresses have been determined in the result of the stress states analyses. The obtained results enable to identify the optimal geometric and kinematic parameters, in case of which the sliding cutting can be implemented with minimum energy consumption.
Keywords: Agricultural Engineering